PERENCANAAN JEMBATAN PENYEBERANGAN ORANG DENGAN STRUKTUR BAJA CASTELLATED DAN STRUKTUR BETON PRATEGANG VOIDED SLAB (Studi kasus Kawasan Industri Rembang Pasuruan Jl. Raya Surabaya-Pasuruan Km 50, Raci, Pasuruan) - Muhammad Ferdian Ramadianto, Sugeng Riyanto, Qomariah (Jurusan Teknik Sipil, Politeknik Negeri Malang, 2014)
The existing traffic conditions at the gate of Pasuruan Industrial Estate Rembang (PIER) located on Surabaya-Pasuruan Highway KM 50, Desa Raci, Bangil, Pasuruan is classified the National Highway type II class 1. It has an average volume of 286 pedestrian / hour (V) and 5175 vehicle / hour (P), so PV2 value is equal to 7.66 x 109. It can be a traffic accident-prone area, especially for pedestrians. Therefore, it needs the facility of Pedestrian Cross Bridge of 17.5 m span and 2.5 m wide. That is why, the writer examines the difference between the two structures in terms of cost. This study comprises planning, detailed engineering design, implementation methods, and cost estimate of castellated steel structures and prestressed concrete voided slab structures.The result of study are as follow : the castellated steel main girder WF 700 x 300 x 13 x 24 at IDR 723,247,800.00 and prestressed concrete voided slab with a size of 970 x 875 diameter 340 mm at IDR 496,282,628.00. From these results, it is concluded that construction of of prestressed concrete voided slab structure is cheaper with price difference IDR 226,965,172.00.Keyword: pedestrian bridge, castellated steel, prestressed concrete voided slab, estimate cost